2007
DOI: 10.1074/jbc.m610536200
|View full text |Cite
|
Sign up to set email alerts
|

Non-enzymatic Glycation of Bone Collagen Modifies Osteoclastic Activity and Differentiation

Abstract: Type I collagen, the major organic component of bone matrix, undergoes a series of post-translational modifications that occur with aging, such as the non-enzymatic glycation. This spontaneous reaction leads to the formation of advanced glycation end products (AGEs), which accumulate in bone tissue and affect its structural and mechanical properties. We have investigated the role of matrix AGEs on bone resorption mediated by mature osteoclasts and the effects of exogenous AGEs on osteoclastogenesis. Using in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
141
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(164 citation statements)
references
References 67 publications
14
141
0
9
Order By: Relevance
“…Our data suggest that high D-Glc interferes with RANKL signaling by reducing ROS production, caspase-3 and NF-κB activation. Recently, advanced glycation end products (AGES) that accumulate with aging in bone tissues of diabetics have been identified as inhibitors of osteoclast formation and resorption [45]. Taken together with our findings, it is possible that high glucose and AGES may act in concert to prevent excessive osteoclast-mediated bone loss in some cases of diabetes.…”
Section: Discussionsupporting
confidence: 78%
“…Our data suggest that high D-Glc interferes with RANKL signaling by reducing ROS production, caspase-3 and NF-κB activation. Recently, advanced glycation end products (AGES) that accumulate with aging in bone tissues of diabetics have been identified as inhibitors of osteoclast formation and resorption [45]. Taken together with our findings, it is possible that high glucose and AGES may act in concert to prevent excessive osteoclast-mediated bone loss in some cases of diabetes.…”
Section: Discussionsupporting
confidence: 78%
“…Preparation of AGE-BSA protein AGE-BSA was prepared according to a modified version of a previously described protocol (Valcourt et al, 2007). BSA (50 mg/ml; Fraction V, Sigma, St. Louis, MO) was incubated with 0.6 M D-ribose and incubated at 37 o C for one week in phosphate-buffered saline (PBS) containing 100 U/ml penicillin and 100 μg/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…18 In contrast, in another study in which human osteoclasts were seeded on bone slices, treated with a high dose of exogenous ribose, the activity of human osteoclasts was decreased. 19 Such discrepancies are most likely related to differences in the model used, and also in the concentration of AGEs within the bone. A recent study that analyzed the relationship between AGEs and osteoclast activity in human cadaveric bone specimens showed that higher AGEs was associated with an increased number of larger resorption cavities.…”
Section: Figurementioning
confidence: 99%